Representation of women in Malaysian literature in English - Muslim, Mazni; Abdul Manaf, Nor Faridah; Abdillah, Nasirin; Abdul Rahman, Roslina (UPENA, UiTM Trengganu, 2011)
The article looks at the representation of women in Malaysian literature in English by three Malay Muslim writers: Dina Zaman, Che Husna Azhari and Ellina Majid.